THE USE OF ANIMATED SHORT FILM AS MEDIA FOR TEACHING ENGLISH TO OPTIMIZE STUDENTS WRITING SKILLS: (A Classroom Action Research at Tenth Grade of MAN 1 Surakarta in 2023/2024 Academic Year) - Saraswati, Trianni Dewi; Al Hakim, Luqman (ENGLISH RESEARCH JOURNAL, 2025)
This research aimed to: (1) describe the implementation of animated short films in teaching narrative writing at the tenth grade of MAN 1 Surakarta in the 2023/2024 academic year, and (2) identify whether the use of animated short films improves students' logical sequence of ideas in writing narrative texts. The study employed Classroom Action Research, conducted in two cycles during the August 2023/2024 academic year with the participation of XE4 students. Data collection methods included tests, observations, interviews, questionnaires, and documentation. Data analysis utilized both qualitative (Miles and Huberman's model) and quantitative (mean scores) methods. The results revealed that animated short films significantly enhanced students' logical sequencing in narrative writing. The students’ average scores improved from 62 in the pre-test to 74 in post-test 1, and 77 in post-test 2. Thus, animated short films effectively improved students’ narrative writing skills, particularly in organizing logical story sequences. Keywords: Writing Skills, Animated Short Films, Classroom Action Research.